The effect of professionalism and locus of control on the auditor’s job performance with working motivation as intervening variable - Alex Dwiputra Siregar; Joicenda Nahumury (Universitas Hayam Wuruk Perbanas, 2015)
This research aims to analyze the effect of professionalism and locus of control on the auditor’s job performance using work motivation as intervening variable. This study uses primary data obtained by distributing questionnaires to auditors who work at Audit Firms in Surabaya area listed on the Audit Firms (KAP) Directory issued by the Institute of Indonesia Chartered Accountants (IAPI) in 2010. The sampling is using convenience-sampling method, while the data analysis method is using path analysis. The result of path analysis test shows that (1) professionalism has an effect on the value of job performance (2) professionalism has no significant effect on the value of job performance with work motivation as an intervening variable (3) locus of control has no significant effect on the auditor’s job performance (4) locus of control has significant effect on the auditor’s job performance with work motivation as an intervening variable.